OPTIMALISASI KINERJA PERSIMPANGAN TIDAK SEBIDANG PADA KAWASAN PERBELANJAAN MALL SKA – LIVING WORLD (SIMPANG JL. TUANKU TAMBUSAI – JL. SOEKARNO HATTA) DI PEKANBARU: OPTIMALISASI KINERJA PERSIMPANGAN TIDAK SEBIDANG PADA KAWASAN PERBELANJAAN MALL SKA – LIVING WORLD (SIMPANG JL. TUANKU TAMBUSAI – JL. SOEKARNO HATTA) DI PEKANBARU - Ridwan Helmi (LPPM Universitas Abdurrab, 2023)
Intersection Jl. Tuanku Tambusai – Jl. Soekarno - Hatta is a non-level APILL intersection which is in the SKA - Living World Mall Shopping Area, Peaknbaru City. Existing performance at Simpang Jl. Tuanku Tambusai – Jl. Soekarno - Hatta namely degree of saturation 1.05, intersection delay 645.5 seconds, and queue 371.10 m. This study aims to analyze the existing conditions using the PTV Vissim application simulation and the application of alternative scenarios for handling the problem. From the results of the analysis obtained several alternative scenarios for handling traffic problems at the Jl Intersection. Tuanku Tambusai – Jl. Soekarno - Hatta namely the diversion of traffic conflicts in scenario 1, setting the cycle time in scenario 2 and widening the road in scenario 3